Sobre potenciação:
(4^5 . 2^-2)^3=
Usuário anônimo:
Quando for elevado, coloca (^)
Soluções para a tarefa
Respondido por
1
.
![(4^5.2^{-2)^3}=[(2^2)^5.2^{-2}]^3=(2^{10}.2^{-2})^3=(2^{10-2})^3=(2^8)^3=2^{24} (4^5.2^{-2)^3}=[(2^2)^5.2^{-2}]^3=(2^{10}.2^{-2})^3=(2^{10-2})^3=(2^8)^3=2^{24}](https://tex.z-dn.net/?f=%284%5E5.2%5E%7B-2%29%5E3%7D%3D%5B%282%5E2%29%5E5.2%5E%7B-2%7D%5D%5E3%3D%282%5E%7B10%7D.2%5E%7B-2%7D%29%5E3%3D%282%5E%7B10-2%7D%29%5E3%3D%282%5E8%29%5E3%3D2%5E%7B24%7D)
Perguntas interessantes
Física,
1 ano atrás
História,
1 ano atrás
Inglês,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Sociologia,
1 ano atrás